Interaksi Hukum dan Sains dalam Siklus Kebijakan Baku Mutu Udara Ambien - Cecep Aminudin; Refial Fadly; Hermawan (Jurnal Ekologi, Masyarakat dan Sains, 2021)
Environmental standards such as the Ambient Air Quality Standard (AAQS) is the core of environmental law especially that uses a command and control approach. Scientific considerations are very important in determining the AAQS although they are not the only thing considered. This article aims to elaborate further the interaction of law and science in the AAQS policy cycle. There are opportunities for the interaction of law and science throughout the AAQS policy cycle that can contribute to better environmental policy and law. Effective science and law communication is one of the essentials factor for a more fruitful interaction.